Reasonable Timing of Radiotherapy for Stage IV Non-Small-Cell Lung Cancer During Targeted Therapy Based on Tumour Volume Change - Li, Qingsong; Liang, Na; Zhang, Xia; Zhang, Yi; Ouyang, Weiwei; Su, Shengfa; Ma, Zhu; Hu, Yinxiang; Geng, Yichao; Chen, Xiaxia; Lu, Bing (Frontiers in Oncology, 2021)
Purpose The aim of this study was to investigate the reasonable timing of radiotherapy for stage IV non-small-cell lung cancer (NSCLC) with EGFR-positive mutations during targeted therapy based on tumour volume change (TVC). Patients and methods Simulation Computed Tomography Scan (SCTS) measurements were taken to test TVC in patients with stage IV NSCLC during targeted therapy at intervals of 10 days. The SCTS measurement was terminated when the tumour volume shrinkage rate in the latter simulation compared with the previous simulation was ≤5% or when the time after treatment was 90 days. Then, primary tumour radiotherapy was performed. Related parameters of the radiotherapy plan were compared between the implementation and simulation plans. Results Twenty-seven patients were enrolled in the analysis. After treatment, shrinkage of the primary tumour was observed in all patients, but the rate and speed were inconsistent. The average tumour volume decreased obviously within 40 days and was significantly different every 10 days (P≤0.001). The average volume decreased slowly and tended to be stable (P>0.05) after 40 days. After the termination of SCTSs, 21 patients accepted primary tumour radiotherapy. No patients experienced grade 3+ acute radiation toxicity. The implementation radiotherapy plan was significantly better than that before treatment (all P<0.05) but not better than that on the 40th day after treatment (all P>0.05). Conclusions To obtain a high radiation dose and control radiation toxicity, the 40th day after targeted therapy may be a reasonable time to start radiotherapy for stage IV NSCLC with EGFR-positive mutations.